Investigation of annealing effects on the physical properties of Ni0.6Zn0.4Fe1.5Al0.5O4 ferrite. Issue 35 (26th June 2019) - Lahouli, R.; Massoudi, J.; Smari, M.; Rahmouni, H.; Khirouni, K.; Dhahri, E.; Bessais, L.
Abstract : In the present study, the structural, morphological, electrical, and dielectric properties of Ni0.6 Zn0.4 Fe1.5 Al0.5 O4 annealed at 600 °C, 900 °C, and 1200 °C were investigated. Abstract : In the present study, the structural, morphological, electrical, and dielectric properties of Ni0.6 Zn0.4 Fe1.5 Al0.5 O4 annealed at 600 °C, 900 °C, and 1200 °C were investigated. The X-ray diffraction patterns confirmed the presence of the single-phase cubic spinel structure with the Fd 3̄ m space group. The SEM images of Ni0.6 Zn0.4 Fe1.5 Al0.5 O4 nanoparticles demonstrated that these samples (Ni900 and Ni1200) were nano-sized and that the increase in annealing temperature enhanced the agglomeration rate. It was found that the electrical conductivity of the system improved on increasing the temperature over the whole explored range for the two low annealing temperatures, while this improvement declined after 500 K in the case of the highest annealing temperature. For such a sample, a metallic behavior was seen. The sample annealed at 1200 °C possessed the highest conductivity and the lowest activation energy. The impedance measurements were in good agreement with the conductivity plots and confirmed the emergence of a grain boundary effect with the increase in annealing temperature. For the sample annealed at the highest temperature, Z ′ decreased rapidly with frequency. This sample exhibited the lowest defect density than the other samples. Consequently, its electrical conductivity increased. A Nyquist diagram was used to examine the contribution of the grains and grain boundary to conduction and to model each sample by an equivalent electrical circuit. The dielectric behavior of the investigated samples was correlated to the polarization effect.